Cellular Nanoscale Sensory Wave Computing - Baatar, Chagaan.; Porod, Wolfgang.; Roska, Tams̀. (Springer US, 2010)
In this book the emerging and converging architecture of morphic cellular wave computers based on the concept of Cellular Neural/Nonlinear Network (CNN) is introduced in a practical way. The authors include descriptions of hardware architectures, software algorithms, as well as a possible new CNN cell based on memristor. The first single chip cellular wave computer- a vision system on a chip (VSoC) is also discussed. Cellular Nanoscale Sensory Wave Computing is a result of a Multidisciplinary University Research Initiative (MURI) project that has been funded by the Office of Naval Research and completed recently. The results manifest a new way of thinking about sensory computing, as well as it is one of the first successful attempts to bridge the gap between nanoscale (smaller than 100 nm) devices and CMOS integrated circuits with stored programmable algorithms and software on the system level.